2021
DOI: 10.1016/j.esmoop.2021.100232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with HER2-positive breast cancer and development of a nomogram for predicting survival

Abstract: Background Different estrogen receptor (ER) and progesterone receptor (PR) expression patterns have important biological and therapeutic implications in patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer. However, little is known about hormone receptor (HR)-positive and triple-positive subtypes, making therapy selection and survival prognosis difficult. This study investigated the clinical characteristics and nomogram-predicted survival of patients with HER2-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
(54 reference statements)
1
16
3
Order By: Relevance
“…Tumor subtypes were determined based on ER, PR, and HER2 expression profiles after establishing the positivity threshold values for these genes by Gaussian-deconvolution ( Figure 2 A–C). Of the 301 tumor tissues analyzed, the positivity rates were 73.42% for ER, 57.8% for PR, and 10.96% for HER2, in line with previous reports [ 18 , 19 ]. Based on these genes, tumor types were attributed: 68.4% of all tumors were Luminal A subtype, 6% Luminal B, 5% HER2 enriched, and 20.6% Triple Negative.…”
Section: Resultssupporting
confidence: 90%
“…Tumor subtypes were determined based on ER, PR, and HER2 expression profiles after establishing the positivity threshold values for these genes by Gaussian-deconvolution ( Figure 2 A–C). Of the 301 tumor tissues analyzed, the positivity rates were 73.42% for ER, 57.8% for PR, and 10.96% for HER2, in line with previous reports [ 18 , 19 ]. Based on these genes, tumor types were attributed: 68.4% of all tumors were Luminal A subtype, 6% Luminal B, 5% HER2 enriched, and 20.6% Triple Negative.…”
Section: Resultssupporting
confidence: 90%
“…R. Largillier et al ( 16) used a Cox proportional hazards model to identify age, the number of positive lymph nodes, adjuvant chemotherapy, and site of metastasis as independent predictors of stage IV BC patients' OS. Furthermore, liver metastasis, brain metastasis, lung metastasis, high histological grade, and large tumor size were reported to be associated with poor survival (15,18,23). However, all factors mentioned above did not have a prognostic effect on HR +/HER2-ABC patients' OS in our research results.…”
Section: Discussioncontrasting
confidence: 57%
“…Larger tumors are less favorable for patients who wish to preserve their breasts and may often require patients to receive chemotherapy prior to surgery to shrink the tumor before surgery. In addition, one study ( 15 ) found that patients with HR-negative/HER2-positive tumors had more aggressive clinical features, including tumor stages III-IV, T stages 2-4, N stages 1-3, and M stage 1 including brain, liver, and lung metastases, clinical research revealed that BC metastasized mostly to the lung, bone, and liver via circulatory system ( 16 ); In contrast, triple positivity was associated with milder tumor behavior. These results suggest that triple-positive tumors are an independent biological subtype.…”
Section: Discussionmentioning
confidence: 99%